Pseudoneglect for the bisection of mental number lines - Loftus, Andrea; Nicholls, M.; Mattingley, J.; Chapman, H.; Bradshaw, J. (Routledge, 2009)
Patients with unilateral neglect of the left side bisect physical lines to the right whereas individualswith an intact brain bisect lines slightly to the left (pseudoneglect). Similarly, for mental numberlines, which are arranged in a left-to-right ascending sequence, neglect patients bisect to the right.This study determined whether individuals with an intact brain show pseudoneglect for mentalnumber lines. In Experiment 1, participants were presented with visual number triplets (e.g., 16,36, 55) and determined whether the numerical distance was greater on the left or right side of theinner number. Despite changing the spatial configuration of the stimuli, or their temporal order,the numerical length on the left was consistently overestimated. The fact that the bias was unaffectedby physical stimulus changes demonstrates that the bias is based on a mental representation. The leftward bias was also observed for sets of negative numbers (Experiment 2)—demonstrating not onlythat the number line extends into negative space but also that the bias is not the result of an arithmeticdistortion caused by logarithmic scaling. The leftward bias could be caused by a rounding-down effect.Using numbers that were prone to large or small rounding-down errors, Experiment 3 showed noeffect of rounding down. The task demands were changed in Experiment 4 so that participants determined whether the inner number was the true arithmetic centre or not. Participants mistook innernumbers shifted to the left to be the true numerical centre—reflecting leftward overestimation.The task was applied to 3 patients with right parietal damage with severe, moderate, or no spatialneglect (Experiment 5). A rightward bias was observed, which depended on the severity of neglectsymptoms. Together, the data demonstrate a reliable and robust leftward bias for mental numberline bisection, which reverses in clinical neglect. The bias mirrors pseudoneglect for physical linesand most likely reflects an expansion of the space occupied by lower numbers on the left side ofthe line and a contraction of space for higher numbers located on the right.